(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Ridwan R, Rusmana I, Widyastuti Y, Wiryawan KG, Prasetya B, Sakamoto M, Ohkuma M. 2019. Bacteria and methanogen community in the rumen fed different levels of grass-legume silages. Biodiversitas 20: 1055-1062. This study aimed to investigate the effects of dietary grass-legume silages on the microbial community by using a culture-independent approach. Treatments consisted of R0: 50% Pennisetum purpureum and 50 % concentrate; R1: 20% P. purpureum, 50 % concentrate, and 30% grass-legumes silage; R2: 20% P. purpureum, 35 % concentrate, and 45% grass-legumes silage; and R3; 20% P. purpureum, 20 % concentrate, and 60% grass-legumes silage. The rumen fluid obtained from fistulated cattle was used for T-RFLP, 16S rDNA clone library, and qPCR analyses. The results indicated that bacterial diversity was dominated by Bacteroidetes, Firmicutes, and methanogen by Methanobacteriales, based on partial 16S rDNA sequences. The microbial communities were dominated by Prevotella brevis, P. ruminicola, Succiniclasticum ruminis, and Methanobrevibacter ruminantium, M. smithi, M. thueri, and M. millerae. The increasing silage diet in a rumen suppressed methanogenesis by reducing population distribution of Methanobacteriales, directly or indirectly, by reducing the diversity of bacterial populations. Generally, the increase silage in the diet changed the bacterial and methanogen community. Grass-legume silage diets of less than 45% are potential for ruminant diet to reduce methane production by a decrease of 4% in the relative distribution of methanogens in the rumen.